EXTERIOR AND INTERIOR QUALITY OF DUCK EGG STORED DURING 0-28 DAYS IN BEDUGUL HIGHLAND - C. A., Pasaribu; Dewi, G. A. M. K.; Wijana, I W. (Jurnal Peternakan Tropika, 2019)
The purpose of this study is determining the exterior and interior quality of duck egg that was saved during 0-28 days in Bedugul highland. The research and analyzed sample were conducted at Bedugul in Fowl Livestock Laboratory of Faculty of Animal Husbandry of Udayana University for 5 weeks from 30 March until 04 May 2019. The research design used Completely Randomized Design (CRD) which contain 5 treatments, 3 repetition and every repetition contained 5 eggs. The observing variable were exterior quality including egg weight and egg shape index, and interior quality including eggshell weight, eggshell thickness, egg yolk color, haugh unit (HU), and egg pH. The result showed saving egg haugh unit (HU) for 21 eggs pH for 7 days were lower than the control and statistical it showed different result (P<0,05). The result of study in the egg weight, egg shape index, egg shell weight, egg shell thickness, and egg yolk color showed there was no significant different (P>0,05). Based on the research, it can be conclude that saving duck egg during 21 daysat room temperature 18? in the night and 21? in the noon in highland of Bedugul consisted decreasing quality at the point of haugh unit (HU) and saving egg in 7 days consisted decreasing quality in egg pH, but there was no affecting to the egg weight, egg shape index, egg shell weight, egg shell thickness and egg yolk color. This case showed that duck egg still in good quality and proper to consume after saving during 28 days with grade A in the eggs   Key points: duck egg, saving time, highland, exterior and interior quality